Lunch walks among us - Benton, Jim (New York : Simon & Schuster Books for Young Readers, 2011)
Franny K. Stein is a mad scientist who prefers all things spooky and creepy, but when she has trouble making friends at her new school she experiments with fitting in--which works until a monster erupts from the trashcan.
Reprint. Originally published: c2003.
Keywords: Monsters -- Fiction; Science -- Experiments -- Fiction; Schools -- Fiction; Identity -- Fiction; Monsters -- Fiction; Science -- Experiments -- Fiction; Identity (Psychology) -- Fiction; School stories; Humorous fiction; Humorous fiction